Nietzsche-Studien : Internationales Jahrbuch für die Nietzsche-Forschung (De Gruyter, 1973)
Nietzsche-Studien is the world's leading organ for Nietzsche research. It publishes contributions from all disciplines that deal with Nietzsche's life, work, and impact and spotlights the relevance of his thought for current debates. It is not committed to any particular school of thought and features essays, discussions, documentary research, investigations of primary sources, contributions to reception studies, miscellanea, and reviews.